Characterizing the Risk and Outcome Profiles of Lumbar Fusion Procedures in Patients With Opioid Use Disorders: A Step Towards Improving Enhanced Recovery Protocols for a Unique Patient Population. (1st September 2019) - Martini, Michael L; Nistal, Dominic A; Deutsch, Brian C; Gilligan, Jeffrey; Rothrock, Robert J; Neifert, Sean N; Caridi, John M
Abstract: INTRODUCTION: This national-level study sought to provide a necessary assessment of the risks and outcomes for different lumbar fusion procedures in patients with opioid use disorders (OUDs) to help guide the future development of targeted enhanced recovery after surgery (ERAS) protocols for this unique population. METHODS: Data for patients with or without OUDs who underwent an anterior lumbar interbody fusion (ALIF), posterior lumbar interbody fusion (PLIF), or lateral transverse lumbar interbody fusion (LLIF) for lumbar disc degeneration (LDD) were collected from the 2013 to 2014 National Inpatient Sample. Multivariable logistic regression was implemented to analyze how OUD impacted in-hospital complications, length of hospitalization, discharge disposition, and total charges by procedure type. RESULTS: A total of 139 995 patients with LDD were identified, with 1280 patients (0.91%) also having a concurrent OUD diagnosis. Overall complication rates were higher in OUD patients (48.44% vs 31.01%; P  < .0001). OUD patients had higher odds of pulmonary ( P  = .0006), infectious ( P  < .0001), and hematological complications ( P  = .0009). Multivariate regression modeling of outcomes by procedure type showed that following ALIF, OUD increased odds of nonhome discharge ( P  = .0007), extended hospitalization ( P  = .0002), and greater total charges ( P  = .0054). This analysis also revealed that OUD increased odds of complication ( P  = .0149 and P  = .0471), extended hospitalization ( P  = .0439 and P  = .0001), and higher total charges ( P  < .0001) following PLIF and LLIF procedures, respectively. CONCLUSION: Obtaining a better understanding of the risks and outcomes that OUD patients face perioperatively is a necessary step towards developing more effective ERAS protocols for this vulnerable population. This study, which sought to characterize outcome profiles for lumbar fusion procedures in OUD patients on a national level, found this population experienced increased odds of complication, extended hospitalization, nonhome discharge, and higher total charges. Results from this study warrant future prospective studies to better understand these associations and further the development of ERAS programs to improve patient care and reduce cost burden.